Correlações entre os caracteres estruturais determinantes dos hábitos de crescimento das cultivares de feijão - Pinheiro, Lucas Rezende (2014)
The aim of this study was to evaluate cultivars with different growth habits, in the main planting seasons in southern Minas Gerais, in order to identify changes in the main morphological and agronomic characters in relation to the classification used to measure the correlation between morphological and agronomic traits related to growth habit of the bean and to evaluate the anatomical differences and their association with morpho-agronomic traits. The experiments were performed in six seasons in the years 2012 and 2013 in a randomized block design with three replications. Assays were composed of 20 different genotypes of the four types of growth habit. Data from 13 morphological characters in all seasons and 20 anatomical characters in the dry season of 2013 were obtained.The characters that best separated the genotypes according to their growth habits were growth grade, length of main stem, number of nodes on the main stem, stem diameter and weight of 100 grains. The year effect was not significant only for the length of the main and number of grains per pod rod. The effect of season was also significant for almost all traits, except for habit grade and height of the first pod. The interaction between genotypes and seasons was significant for the characters 50% of flowering plants, length of main stem, number of pods, number of seeds per pod and weight of 100 grains. No character showed significant interaction between genotypes and year. The interaction between year and seasons was not significant onlyforgrowth habit, number of pods and stem diameter. Most important characters to the growth habit for the water seasons were the length of the main stem, number of nodes on the main stem, the average internode length and stem diameter, so the higher the rating (best size) less plant height, number of nodes on the main stem, the average length of internodes and larger stem diameter. Most important characters to the growth habit for the seasons dry/winter were the length of the central stem and stem diameter.In the water seasons, there is a greater proportional influence of genetic effects on the expression of the characters. The differences in anatomical characters were not able to separate the genotypes according to their types of growth habit. Only for the average length string of the rib of the sheet, the total thickness of the sheet width and the xylem of the stem usual types were divided into 4 groups, one for each type of growth habit, with the usual type I showed lower ELF and greater type IV. The pool by the Mahalanobis distances not formed groups according to growth habit. The note size is highly correlated with the overall diameter and the exchange of the stem. Overall anatomical characters were not correlated with different growth habits.